Modified differential evolution algorithm for simple assembly line balancing with a limit on the number of machine types. Issue 2 (1st February 2016) - Pitakaso, Rapeepan; Sethanan, Kanchana
Abstract : This article proposes the differential evolution algorithm (DE) and the modified differential evolution algorithm (DE-C) to solve a simple assembly line balancing problem type 1 (SALBP-1) and SALBP-1 when the maximum number of machine types in a workstation is considered (SALBP-1M). The proposed algorithms are tested and compared with existing effective heuristics using various sets of test instances found in the literature. The computational results show that the proposed heuristics is one of the best methods, compared with the other approaches.